2021
DOI: 10.3390/math9070707
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearities and Chaos: A New Analysis of CEE Stock Markets

Abstract: After a long transition period, the Central and Eastern European (CEE) capital markets have consolidated their place in the financial systems. However, little is known about the price behavior and efficiency of these markets. In this context, using a battery of tests for nonlinear and chaotic behavior, we look for the presence of nonlinearities and chaos in five CEE stock markets. We document, in general, the presence of nonlinearities and chaos which questions the efficient market hypothesis. However, if all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Moreover, a panel study for 33 countries in developed countries in the period of 1992-2018 using panel root tests provides strong evidence for the weak-form efficiency of stock markets. These results were later refuted by another study done in five central and east European countries using run tests that revealed chaotic and nonlinearity in indices returns which questions the validity of EMH in these countries (Albulescu, Tiwari, & Kyophilavong, 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, a panel study for 33 countries in developed countries in the period of 1992-2018 using panel root tests provides strong evidence for the weak-form efficiency of stock markets. These results were later refuted by another study done in five central and east European countries using run tests that revealed chaotic and nonlinearity in indices returns which questions the validity of EMH in these countries (Albulescu, Tiwari, & Kyophilavong, 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 94%
“…Conducting event study methodology can be done generally following two main approaches; the first is to determine the pre and postperiod time intervals and then the date of the event and afterwards abnormal returns following immediately the event occurrence will be calculated (Albulescu, Tiwari, & Kyophilavong, 2021). Hence, the volatility of the market is to be examined over the short-, medium-and long-term using the rolling window regression approach and the chosen event window is to be determined according to the study.…”
Section: Methodsmentioning
confidence: 99%
“…x * 3 (11) where: x * 1 , x * 2 , and x * 3 are the desired states. We substituted (11) in (10) and considered defining the errors:…”
Section: Integer Order Systemmentioning
confidence: 99%
“…Following this trend, the number of investigations seeking to explain the influence of structural variations, uncertainties in microeconomic and macroeconomic variations, irregular increases, and effects of parameters on the dynamics of financial and economic systems has grown, as well as the emergence of chaotic behavior [8,9]. The non-linearities and chaotic behavior of stock markets have been investigated by [10,11]. The authors concluded that the analyzed action systems have a chaotic behavior and that their non-linearities must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, any government action may induce additional uncertainty [36], which in turn, leads to an increase in the volatility of government bond markets. On the other hand, several other papers consider government interventions as responsible actions that may curb the adverse effects of crises and uncertainty [37][38][39], which can also be the case for sovereign debt.…”
Section: Introductionmentioning
confidence: 99%